Striping within the network subsystem. - Traw, C.B.S (IEEE Network : the magazine of global information exchange)
Striping is a general architectural technique for the, transparent aggregation of multiple, functionally similar, resources to obtain higher performance. This article establishes a precise terminology for discussing striping and striping techniques, differentiates striping from the more general architectural technique of multiplexing, and outlines the major uses and trade-offs associated with the technique within the network subsystem. It presents a set of criteria for evaluating network striping and a case study of striping within a typical high performance network stack consisting of TCP/IP over ATM/SONET. IT also includes a set of ?rules of thumb? for the inclusion of striping within the network subsystem. An appendix describes the trace driven simulation used to support the case study